Forming the Strategy of Financial Development for Highly Technological Enterprise - ZHURAVEL, Vitaly; KOSTYUKOV, Konstantin; BATISHCHEVA, Elena; EL’CHANINOVA, Olga; LESHCHEVA, Marina (Journal of Advanced Research in Law and Economics; Vol 8 No 6 (2017): JARLE Volume VIII Issue 6(28) Fall 2017, 2017)
The article aims at forming methodic recommendations that allow to efficiently apply modern tools to manage finances when implementing the strategy of a highly technological enterprise. This area is urgent due to specific peculiarities of forming the management program by research and development companies in the context of external economic activity and consequently a special competitive environment of functioning. In this regard, the research improves methodic approaches to forming target problem blocks and develops the mathematic block of defining a synergetic effect of the offered areas for implementing. The offered approach is based on the diagnostics of the ‘weakest’ points of the enterprise internal system, further recommendations on eliminating them, and comparing the results with the adaptive scenarios of the following functioning of the RDE. The authors have formed the morphological and economic interpretation of the determined blocks, and made an expert and economic and mathematic estimation of the offered measures. The research novelty is related to applying the adaptive and scenario approach when stipulating recommendations on the combined use of tools to manage financial resources of the enterprise. Questionnaire forms have been developed to obtain expert estimations and opinions. The aggregate of recommendations and results is an important supplement to the methodology of the strategy of financial enterprise of the highly technological enterprise.